2016
DOI: 10.1016/j.epsl.2016.02.054
|View full text |Cite
|
Sign up to set email alerts
|

Halogen (F, Cl, Br, I) behaviour in subducting slabs: A study of lawsonite blueschists in western Turkey

Abstract: We examined the F, Cl, Br and I abundance of minimally retrogressed lawsonite blueschists from the Tavsanli Zone in northwest Turkey to evaluate the behaviour of halogens in subduction zones, and to determine the role coexisting high pressure minerals may play in transporting the halogens to the Earth's mantle. The blueschists contain sodic amphibole and lawsonite, with variable amounts of phengite and chlorite, and minor apatite. A positive correlation between Cl, Br and I contents in bulk rocks suggests thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 46 publications
5
27
1
Order By: Relevance
“…Recent studies have suggested that up to ~90% of non-radiogenic Ar, Kr and Xe and most of the heavy halogens (Cl, Br, I) have subducted origins in the Earth's mantle (Holland and Ballentine, 2006;Holland et al, 2009;Mukhopadhyay, 2012;Caracausi et al, 2016;Kendrick et al, 2017). However, relatively few studies have investigated the combined behaviour of multiple halogens and/or noble gases during prograde metamorphism (John et al, 2011;Kendrick et al, 2015;Pagé et al, 2016;Pagé and Hattori, 2017),…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested that up to ~90% of non-radiogenic Ar, Kr and Xe and most of the heavy halogens (Cl, Br, I) have subducted origins in the Earth's mantle (Holland and Ballentine, 2006;Holland et al, 2009;Mukhopadhyay, 2012;Caracausi et al, 2016;Kendrick et al, 2017). However, relatively few studies have investigated the combined behaviour of multiple halogens and/or noble gases during prograde metamorphism (John et al, 2011;Kendrick et al, 2015;Pagé et al, 2016;Pagé and Hattori, 2017),…”
Section: Introductionmentioning
confidence: 99%
“…Kendrick, Jackson, et al () accounted for the uniform and relatively low I/Cl ratio of the mantle by suggesting that addition of the hydrated oceanic lithospheric mantle with high I/Cl ratio is balanced either by subduction of Cl‐rich materials such as AOC (Chavrit et al, ; Kendrick, Honda, et al, ) or by the preferential loss of I from subducting slabs at relatively shallow depths (John et al, ; Kendrick et al, ; Pagé et al, ). However, there is support for I‐rich halogen subduction beneath and beyond sub‐arc depth.…”
Section: Discussionmentioning
confidence: 99%
“…The distorted Ca site and multiple Al sites of monoclinic laswonite also have implications for the geochemical partitioning behavior of elements at depth and during dehydration. Halogen partitioning in subducting slabs is complex, and lawsonite does incorporate trace amounts of F, Cl, Br, and I [ Pagé et al ., ]. Indeed, upon apatite decomposition at ~200 km, F has been proposed to be sequestered in lawsonite and phengite [ Pagé et al ., ].…”
Section: Geophysical Implicationsmentioning
confidence: 99%
“…Halogen partitioning in subducting slabs is complex, and lawsonite does incorporate trace amounts of F, Cl, Br, and I [ Pagé et al ., ]. Indeed, upon apatite decomposition at ~200 km, F has been proposed to be sequestered in lawsonite and phengite [ Pagé et al ., ]. Thus, lawsonite and phengite represent two of the few minerals that may transport F to depths greater than 200 km.…”
Section: Geophysical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation